Digitalization of Land Certification: Legal Perspectives from Islamic, Positive, and Administrative Law - Anggriani, Jum; Noviarita, Heni; Said, Hasani Ahmad; M. Nainin, Dasrizal (Institut Agama Islam Negeri Curup, 2025)
This research examines the digitalization of land certification from an integrative perspective between Islamic law, positive law, and state administration practices in Indonesia. Digital transformation in the land sector is a strategic urgency to address classic challenges such as agrarian conflicts, overlapping ownership, and administrative inefficiencies. However, the success of digitalization does not only depend on technical aspects, but also on the harmonization of the religious values ​​of society, especially those based on Islamic law and the formal legal system of the state. Through a normative juridical approach, this study explores the meeting points and potential conflicts between the principles of maqāṣid syarI'ah, the principles of Indonesia law as stated in the Basic Agrarian Regulations (UUPA) and its derivative regulations, as well as the principles of good governance in public administration. The results of the study indicate that digitalization can increase legal certainty and efficiency, but still faces challenges such as the gap in digital infrastructure, legal and technological literacy of the community, and disharmony in regulations related to proof of rights, inheritance, and waqf. This research offers a three-dimensional legal integration model as a conceptual solution to realize effective, inclusive, and equitable digitalization of land certification, and is in line with the diversity of social and cultural values ​​of the Indonesian people. This reesarch offers a multidisciplinary legal framework for digital land governance that bridges Islamic and secular law. It provides a model relevant for countries with plural legal systems or large Muslim populations, and serves as a reference for international agencies in formulating culturally responsive and legally coherent land digitalization policies.